ANALYSIS OF LEARNING PROCESS ON HEREDITARY TOPICS IN BIOLOGY SUBJECT AT SMP NEGERI 2 LENGAYANG KABUPATEN PESISIR SELATAN - Destaria Sudirman (Universitas Riau Kepulauan, 2013)
The learning process can influence the student’s learning achievement that is the lower of students’ understanding of a subject. The lower of students’ understanding of a subject is a problem that can disturb student’ learning achievement. The lower of students’ understanding can happen in the learning process of the heredity. This research was aimed to analyze the learning process in Biology on Heredity topics at SMP Negeri 2 Lengayang Kabupaten Pesisir Selatan which involved planning, conducting, and evaluating the learning process.The research which was conducted at SMP Negeri 2 Lengayang Kabupaten Pesisir Selatan was a descriptive research which used qualitative approach. The sample of this research was class IX A (the third year students in group A) and class IX F (the third year students in group F). The data was gotten through observation, interview, and questionnaires. In collecting the data, the researcher used observation sheet which referred to the Regulation of National Education Ministry Number 41 Year 2007 about the standard process for primary and high educational level. Interview was conducted in order to get the data which could not be gotten through observation. Questionnaire was administered to the students to see their alertness and understanding in learning process, while video recording was used to describe the learning process.Based on the result of the research, it was known that (1) lesson plan designed by the teacher had not yet referred to the Regulation of National Education Ministry Number 41 Year 2007, (2) the learning process conducted by the teacher which involved time allocation, learning method, learning model and learning steps had not yet based on the lesson plan designed by the teacher, and (3) the learning evaluation had not yet referred to the Regulation of National Education Ministry Number 41 Year 2007 since the teacher did evaluation only on cognitive aspect.